INDONESIA’S URGENCY IN ADOPTING GOVERNMENT REGULATION CONCERNING SMALLHOLDER-ENTERPRISE PARTNERSHIP: KEBUTUHAN MENDESAK INDONESIA DALAM MENGADOPSI PERATURAN PEMERINTAH TENTANG KERJA SAMA ANTARA PETANI KECIL DAN USAHA KECIL - Yenny, Oktavani; Simbolon, Putu George Matthew (Pusat Studi Konstitusi dan Perundang-undangan, 2025)
This research aims to provide a solution for the Indonesian Crude Palm Oil Smallholders so that they can play on the same level playing field and may acquire international market access. Such urgency exists since a conflict of interest exists between the Indonesian Ministry of Industry and the Ministry of Agriculture in efforts to regulate the KBLI 10431 sector regarding the CPO palm oil industry. In aiming for this purpose, this research is implementing the normative method through the implementation of Indonesian regulations related to industries, agriculture, and trades. This method is also implemented by applying the rules of international trade law. The article herein consists of two discussions involving Indonesia's domestic regulations and Indonesia's compliance with the World Trade Organization. The first discussion explains Indonesia’s necessity to adopt regulations that accommodate the interests of the ministries of industry, agriculture, and trade. The second discussion explains Indonesia's urgency to adopt the government regulation therein due to the urgency in responding to unilateral environmental acts imposed by developed countries. From these discussions, this article recommends that the Indonesian government adopt a government regulation that may reconcile the conflicting interests within its executive branches. The article herein also stresses the urgency of adopting such a regulation to minimize Indonesia's climate litigation in the WTO Dispute Settlement Body.